2009
DOI: 10.1016/j.jphotobiol.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mitochondrial respiratory chain activity in muscle healing by low-level laser therapy

Abstract: These results suggest that the treatment with low-level laser may induce an increase in ATP synthesis, and that this may accelerate the muscle healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 24 publications
6
115
0
15
Order By: Relevance
“…Commonly used modalities to help recovery, such as mas- ous studies have also demonstrated that LLLT can stimulate the mitochondrial respiratory chain and ATP synthesis. 20,29 Such effects could, in turn, contribute to a decrease in CK activity, CRP levels, and also the delay in development of fatigue seen in the current study. Some evidence suggests that other therapies such as massage 39 and hot-cold water baths 15 may prevent muscle damage after exercise.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Commonly used modalities to help recovery, such as mas- ous studies have also demonstrated that LLLT can stimulate the mitochondrial respiratory chain and ATP synthesis. 20,29 Such effects could, in turn, contribute to a decrease in CK activity, CRP levels, and also the delay in development of fatigue seen in the current study. Some evidence suggests that other therapies such as massage 39 and hot-cold water baths 15 may prevent muscle damage after exercise.…”
Section: Discussionmentioning
confidence: 69%
“…6 Studies performed in animals have shown positive effects of LLLT in the form of inflammatory reduction and improvement in muscle repair when the optimal parameters of irradiation were used. 1,8,24,31 Studies into the mechanisms behind these effects suggest that LLLT can decrease oxidative stress and reactive oxygen species production, 2,27 improve mitochondrial function, 37 and stimulate mitochondrial respiratory chain, ATP synthesis, 29 and microcirculation. 34 These effects provides the rationale for testing if LLLT can prevent the development of skeletal muscle fatigue and enhance recovery.…”
mentioning
confidence: 99%
“…Due to the proven ability of red-infrared (IR) radiation to enhance cell energy metabolism (Silveira et al 2009) and reduce inflammation (Rizzi et al 2006), laser therapy is already used in physical medicine, rehabilitation and sports medicine to accelerate muscle recovery (dos Santos et al 2010) and to prevent damages produced by metabolic disturbances and inflammatory reactions after heavy exercise (Leal Junior et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…De fato, a literatura mostra que a LLLT (AsGa; λ 904nm; 5J/cm 2 ) aumentou significativamente a atividade de succinato desidrogenase mitocondrial em músculo esquelético após injúria, além de ter influenciado positivamente também os complexos I, II, III e IV da cadeia respiratória (261) .…”
Section: Discussionunclassified
“…Isto porque um aumento da atividade das mitocôndrias leva à consequente geração de ATP e aceleração do metabolismo celular (261) , tornando-se importante para a reparação tecidual frente a injúrias, por exemplo (268)(269)(270) .…”
Section: Discussionunclassified